2021
DOI: 10.3390/nu13062107
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Dietary Intake Affects the Altered Pattern of Gut Microbiome by Acarbose in Patients with Type 2 Diabetes

Abstract: The aim of this research was to reveal the characteristics of gut microbiome altered by acarbose intervention in Japanese patients with type 2 diabetes (T2D) and its possible association with habitual dietary intake. Eighteen patients with T2D were administered acarbose for four weeks. The abundances of two major phyla, namely Actinobacteria and Bacteroidetes, were reciprocally changed accompanied by the acarbose intervention. There were also significant changes in the abundances of ten genera, including the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“… 105 Consistent with a study in mice, acarbose treatment increased the abundance of Bifidobacterium, Eubacterium , and Lactobacillus and decreased the abundance of Bacteroides in T2D patients. 106 Similarly, the gut microbiota Bifidobacterium longum and Enterococcus faecalis were increased significantly after 4 weeks of acarbose treatment in T2D patients. 107 …”
Section: Anti-aging Interventions and Intestinal Microbesmentioning
confidence: 90%
“… 105 Consistent with a study in mice, acarbose treatment increased the abundance of Bifidobacterium, Eubacterium , and Lactobacillus and decreased the abundance of Bacteroides in T2D patients. 106 Similarly, the gut microbiota Bifidobacterium longum and Enterococcus faecalis were increased significantly after 4 weeks of acarbose treatment in T2D patients. 107 …”
Section: Anti-aging Interventions and Intestinal Microbesmentioning
confidence: 90%
“…In fact, over 95% of the acarbose dose was not absorbed in the gut, coupled with its feature to inhibit microbial α-glucosidases, and subjects’ treatment response to acarbose is dependent on several factors, such as dietary intake, genetic factor, and microbiota composition before treatment (also named enterotypes) ( 62 , 91 93 , 136 , 142 , 143 ). The acarbose-shaped gut microbial composition might be related to the dietary intake in a small Japanese population with T2DM ( 92 ). Moreover, hierarchical clustering showed that the habitual dietary intake of sucrose, fat, and carbohydrate was associated with three distinct microbial clusters, and even the abundance alteration of Faecalibacterium was positively related to dietary rice intake but negatively related to bread intake ( 92 ).…”
Section: The Effects Of Oral Antidiabetic Drugs On Gut Microbiota And...mentioning
confidence: 99%
“…The acarbose-shaped gut microbial composition might be related to the dietary intake in a small Japanese population with T2DM ( 92 ). Moreover, hierarchical clustering showed that the habitual dietary intake of sucrose, fat, and carbohydrate was associated with three distinct microbial clusters, and even the abundance alteration of Faecalibacterium was positively related to dietary rice intake but negatively related to bread intake ( 92 ). A previous study also found that patients with a gut flora driven by Bacteroides displayed more beneficial modifications in gut microbiota, plasma BA composition, and more metabolic metabolism enhancement after acarbose treatment than those with Prevotella ( 62 ).…”
Section: The Effects Of Oral Antidiabetic Drugs On Gut Microbiota And...mentioning
confidence: 99%
“…Other researchers had reported that habitual dietary consumption caused changes in the composition of gut microbiota which in turn influenced the effects of their drug therapy. In Japanese patients with T2D taking acarbose, high rice intake was associated with the abundance of Faecalibacterium while high intake of potatoes was associated with a low abundance of health-promoting microbiota such as Akkermansia and Subdoligranulum ( 77 ). In another human study, compared to 20 obese women before metformin treatment, an increase of Escherichia/Shigella was found after 2 months of low-calorie diet and metformin treatment ( 78 ).…”
Section: Other Factors Affecting Drug-microbiome Interactionsmentioning
confidence: 99%